Socioecological system approach for resilience building. - Udas, Erica. (Tufts University. Tisch Library., 2020)
This presentation covers the use of a socio-ecological system thinking approach for understanding complex drivers of change and building resilient agricultural system.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy